Exploring Learners’ Perceptions of Video-Making Projects in Developing Communicative Competence in English - Baharudin, Muhammad Danial; Mohd Radzi, Khadijah (Pusat Pengajian Citra Universiti (School of Liberal Studies) Universiti Kebangsaan Malaysia, 2024)
Past literature showed that in project-based learning, students actively communicated with their peers in preparing tasks and showed good teamwork skills in completing the objective of the project (Poonpon, 2011; Sevilla-Pavón & Nicolaou, 2017). One of the examples of the tasks that the students can experience under project-based learning is a video-making project (VMP). Since this project involves the use of language both in its process and product, this paper aims to explore learners’ perception of video-making projects in developing their communicative competence in English. Communicative competence is very important as it will lead to increased students’ interest to communicate their ideas (Vorwerg, 2015). Three participants (who have experienced several videomaking projects in their English class) were chosen for this study using purposive sampling. A semi-structured interview was conducted to explore their perceptions on how VMP can develop their communicative competence in English specifically in terms of their linguistic, sociolinguistic, and pragmatic competence. The findings indicated that video-making projects help develop students’ communicative competence in English by allowing students to plan and research correct grammar and sentence structure, thereby reducing errors and enhancing sentence accuracy. It also enhances communication skills through proper and polite interaction with groupmates, guided by instructor feedback to correct mistakes and ensure appropriate behaviour. Future research should examine the impact of video-making projects across diverse settings to further understand their effectiveness in enhancing language skills and communicative competence.